Expression and characterization of a novel cold-adapted chitosanase suitable for chitooligosaccharides controllable preparation. (1st July 2018) - Qin, Zhen; Chen, Qiming; Lin, Si; Luo, Sa; Qiu, Yongjun; Zhao, Liming
Highlights: A novel cold-adapted chitosanase from G. sunshinyii (GsCsn46A) was identified. Characterized a novel single modular GH family 46 chitosanase (GsCsn46A). Cold-adapted property of GsCsn46A can be used for controllable producing COS. Our study provided a cleaner production process for controllable producing COS. Abstract: Chitooligosaccharide is widely used as a functional food additive and a valuable pharmacological agent. The transformation of chitinous biomass into valuable bioactive chitooligosaccharides is one of the most exciting applications of chitosanase. A novel glycoside hydrolase (GH) family 46 chitosanase (GsCsn46A) from rhizobacterium Gynuella sunshinyii was cloned and heterologously expressed in Escherichia coli . GsCsn46A showed maximal activity at pH 5.5 and 30 °C. GsCsn46A featured remarkable cold-adapted property, which controllably hydrolyzed chitosan to three types of chitooligosaccharides at the mild reaction condition (reaction condition: pH 5.5 at 30 °C; method for stopping the reaction: 50 °C for 30 min). The yields of three types of chitooligosaccharides products (degree of polymerization (DP): 2–7, 2–5 and 2–3) were 70.9%, 87.1% and 94.6% respectively. This novel cold-adapted chitosanase provides a cleaner production process for the controllable preparation of chitooligosaccharides with the specific DP.